1985
DOI: 10.1002/1097-0142(19850401)55:7<1513::aid-cncr2820550717>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic localization of estrogen receptors in breast cancer with monoclonal antibodies. Correlation with biochemistry and clinical endocrine response

Abstract: Breast cancer specimens from 114 patients were assayed for the presence of estrogen receptors (ER) utilizing highly specific, monoclonal antiestrophilin antibodies and the peroxidase‐antiperoxidase technique. Results were compared with conventional ER determinations by the dextran‐coated charcoal method (DCC) and were in agreement as to positivity and negativity in 86%. Semiquantifled immunocytologic assay results were in accord with the level of ER as measured by DCC in 66%. The tumors studied included 43 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
3

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(31 citation statements)
references
References 31 publications
1
27
0
3
Order By: Relevance
“…If one wishes to measure the IOD of individual nuclei in frozen sections, extensive programming is required to account for the fact that the majority of cancer nuclei are not sectioned through the greatest diameter of the cell -even if they all could be assumed to be of the same size and shape. As observed by Sklarew & Pertschuk (1987), an important consideration in densitometry of sectioned material is the effect of nuclear volume distribution on the observed receptor concentration (mean optical density). Using nuclear volumes derived from projected nuclear areas, these workers determined that the presence of well-separated concentration peaks could not be ascribed to differences in ER content, but were dependent on variations in nuclear volume.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…If one wishes to measure the IOD of individual nuclei in frozen sections, extensive programming is required to account for the fact that the majority of cancer nuclei are not sectioned through the greatest diameter of the cell -even if they all could be assumed to be of the same size and shape. As observed by Sklarew & Pertschuk (1987), an important consideration in densitometry of sectioned material is the effect of nuclear volume distribution on the observed receptor concentration (mean optical density). Using nuclear volumes derived from projected nuclear areas, these workers determined that the presence of well-separated concentration peaks could not be ascribed to differences in ER content, but were dependent on variations in nuclear volume.…”
Section: Resultsmentioning
confidence: 65%
“…Sensitivity equalled 89% and specificity equalled 100%. This association between ER positivity of breast cancers as analysed by DCC and ERICA (Table III) Pertschuk et al (1985) (80% versus 58%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of immunohistochemistry, antibodies of both polyclonal (Tamura et al, 1984;Lope-Pihie et al, 1985) and monoclonal type (Greene et al, 1980;Coffer & King, 1981) have been generated and amongst these, one in particular (Greene et al, 1980) has been demonstrated to reflect accurately oestrogen receptor (R) status, in several different centres Pertschuk et al, 1985;Hawkins et al, 1986).…”
mentioning
confidence: 52%